An appraisal of Malaysia-China trade relations from the mercantilist perspective - Sivasegaran, Nadarajan (2010)
Despite the emergence of China as a world economic power indicates a positive impact of rising trade opportunities, it also provides threat to other countries especially in the trade balances issue. The trade deficit encountered by Malaysia's in its trade with China certainly reflects China's mercantilist practices which are to achieve favorable trade surplus by applying the instrument of non-tariff barriers in reducing the volumes of Malaysia's export to China. Thus, the main objective of this study is to appraise the problem of trade deficit faced by Malaysia to China from the international political economy perspective of mercantilism in which there are four types of non-tariff barriers that being practices by China to limit the entry of Malaysia's export. These include, Compulsory Product Certification System, Automatic Import Licensing Administration, Standard, Testing and Labeling Requirement, and Quarantine Requirement. In analyzing these non-tariff barriers, Quantity Impact Analysis has been used. This involves the analysis on the quantity of Malaysia's export of products to China from year 2000-2008 in order to determine whether China's non-tariff barriers practices have effect on Malaysia's exports. Based on the findings, China's non-tariff barriers possess negative effects on the quantity of Malaysia's exports to China. Meanwhile in order to face this problem of China's non-tariff barriers, this study further recommends the realization of ASEAN-China Free Trade Agreement and followed by bilateral Free Trade Agreement between Malaysia and China